Et (u)forudseeligt Mellemøsten: Samfundsvidenskaben, point predictions og pattern predictions - Møller, Jørgen (Politik, 2012)
The so-called ‘Arab Spring’ or ‘Arab uprisings’ in 2011 took observers by surprise, thereby reinvigorating the criticism that political scientists are poor at prediction. In this article, it is argued that social science is incapable of predicting such events systematically. e argumentation is based on economist Friedrich Hayek’s distinction between sciences that deals with simple and complex phenomena. e latter category, where the social sciences should be situated, are unable to make ‘point predictions’. What social science can do is to make that which Hayek terms ‘pattern predictions’. Based on established theories within the study of regime change, such pattern predictions are o ered with respect to the longer-term consequences of the Arab uprisings.